2017
DOI: 10.1111/jdi.12713
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of visceral‐to‐subcutaneous fat area predicts cardiovascular events in patients with type 2 diabetes

Abstract: Aims/IntroductionTo investigate whether the ratio of visceral fat area (VFA) to subcutaneous fat area (SFA; V/S ratio) could be predictive of cardiovascular disease (CVD) as compared with VFA or SFA in patients with diabetes.Materials and MethodsA total of 682 patients with type 2 diabetes (mean age 64 ± 13 years; 41% women) were enrolled. VFA (cm2) and SFA (cm2) were assessed by a dual bioelectrical impedance analyzer. The patients were divided into four groups according to the quartiles of the V/S ratio. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 30 publications
0
28
0
1
Order By: Relevance
“…In another cross-sectional study of 408 adults, a larger amount of femoral subcutaneous fat was negatively associated with NAFLD in women, but not in men [25]. VSR can be a useful index to identify individuals at risk of cardiovascular disease [7,8] and metabolic syndrome [15]. Higher VSR, as assessed by a dual bioelectrical impedance analyzer, has been found to be associated with cardiovascular events in patients with type 2 diabetes who regularly visited the university hospital in Tokyo, Japan [7].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In another cross-sectional study of 408 adults, a larger amount of femoral subcutaneous fat was negatively associated with NAFLD in women, but not in men [25]. VSR can be a useful index to identify individuals at risk of cardiovascular disease [7,8] and metabolic syndrome [15]. Higher VSR, as assessed by a dual bioelectrical impedance analyzer, has been found to be associated with cardiovascular events in patients with type 2 diabetes who regularly visited the university hospital in Tokyo, Japan [7].…”
Section: Discussionmentioning
confidence: 96%
“…Although WC is a good general indicator of the total amount of abdominal fat, it does not distinguish between visceral fat and subcutaneous fat, which may have different relationships with metabolic diseases. NAFLD is associated with an increase in visceral fat and a decrease in subcutaneous fat even at identical WC measurements [4][5][6][7][8][9]. Since many studies have reported that visceral fat is a greater contributor to NAFLD development than subcutaneous fat, measurements of the amount of visceral fat in absolute terms or relative to subcutaneous fat have been suggested as indicators of abnormal abdominal fat presence [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Actually, Mahabadi et al reported that visceral fat tissue measured by CT is significantly associated with CVD even after adjusted for the covariates including BMI and WC, indicating the inaccuracy of WC for the measurement of visceral adiposity to estimate future CVD events [ 40 ]. In addition, we previously demonstrated that the ratio of abdominal visceral-to-subcutaneous fat area measured by a dual bioelectrical impedance analyzer independently of cardiovascular risk factors can predict CVD events in patients with type 2 diabetes [ 6 ]. To overcome the defect of WC, a body shape index (ABSI) has been recently developed as a new anthropometric parameter based on WC, BMI and height for the assessment of visceral adiposity [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, visceral adiposity is reported to have greater impact on metabolic abnormalities [ 2 ], CVD [ 3 ], and mortality [ 4 ], compared with total adiposity as usually represented by body mass index (BMI). A recent large-scale prospective study revealed that visceral adiposity has been more useful to predict the risk of CVD than BMI in mostly non-diabetic subjects [ 5 ], and we showed that not BMI but visceral fat accumulation measured by dual bioelectrical impedance analyzer could predict incident CVD in patients with type 2 diabetes [ 6 ]. CVD is the leading cause of death in diabetic patients [ 7 ], therefore, accurate assessment of visceral fat accumulation is critical for assessing the risk of CVD, especially in patients with diabetes.…”
Section: Introductionmentioning
confidence: 93%
“…Besides the overall obesity, the anatomical location of fat also matters in disease development. Studies have shown that intra-abdominal visceral fat is strongly positively correlated with obesity-related diseases, while peripheral subcutaneous fat seems to have no effect or even a protective effect against developing metabolic syndrome [6][7][8][9][10] . However, the biological and genetic differences between visceral and subcutaneous fat are poorly understood.…”
mentioning
confidence: 99%